Health and fitness trends in the post-COVID-19 era in the United Arab Emirates: A cross-sectional study - Alexios Batrakoulis; Željko Banićević; Ivana Banićević; Ashokan Arumugam; Ivan Marović; Nemanja Krstić; Saša Obradović (AIMS Press, 2024)
The health and fitness (H&F) sector is rapidly evolving and appears to be a vibrant space for industry stakeholders with a great potential globally. This observational study aimed to identify the most popular trends related to H&F services in the United Arab Emirates (UAE) for the first time, focused on the industry status after the coronavirus (COVID-19) pandemic, and aimed to detect potential differences with the recent results observed in other countries or regions. Additionally, a chi-square analysis was applied to determine the significant differences between trends and demographics, such as sex, age, experience, and work status. A national online survey was conducted, and applied the methodology of similar international surveys that have been carried out by the American College of Sports Medicine since 2006. In particular, simple random sampling was utilized through an online questionnaire sent to 2771 professionals involved in the UAE's H&F sector. In total, 322 responses were collected with a response rate of 11.6%. The 10 most popular H&F trends in the UAE during the post-COVID-19 era were exercise for weight loss, personal training, traditional strength training, employing certified exercise professionals, boxing, kickboxing, mixed martial arts, youth athletic development, high-intensity interval training, massage, bodyweight training, and wearable technologies. Exercise for weight loss (p = 0.001) and lifestyle medicine (p = 0.032) were more popular among females compared to males, while traditional strength training (p = 0.035) was reported more frequently by males. Going to health clubs and spas (p = 0.001) and practicing yoga (p = 0.011) were more popular trends among middle-aged (36-64 years) respondents compared to young ones (18-34 years). Athletic development (p = 0.042) was more frequently reported by non-practitioners (students) compared to practitioners (part- and full-time employees). The present results are partially in line with those reported in other recent national, regional, and global surveys, which investigated the top H&F trends after the COVID-19 pandemic. Importantly, the main outcomes of this study indicate that the industry stakeholders should focus on in-person H&F services since trends related to technology and digital services are not currently popular nationwide. Moreover, the majority of the top trends were more traditional and rooted activities, which showed that the current status of the H&F sector has established particular training services, programs, and products in the UAE.